Kansas ustilagineae germination - Norton, John Bitting Smith (My University, 1896)
Introduction: The sweets are among the most important fungi to man, economically. Millions of dollars are lost annually on account of their savages among the cultivated crops. The study of their life history has been of great national value to agriculture in providing means of prevention.
Citation: Norton, John Bitting Smith. Kansas ustilagineae germination. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Fungi; Agriculture; Life history; Cultivated crops; Theses; Manuscripts (documents)